PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI DENGAN BUDAYA ORGANISASI SEBAGAI PEMEDIASI PADA SEKOLAH MENENGAH PERTAMA DI WONOSOBO - Pramawati, Dewi Vista; Kuntaryanto, Oki (Widya Dharma Journal of Business - WIJoB, 2023)
This research aims to examine whether organizational culture mediates the relationship between transformational leadership and organizational commitment. 100 respondents are surveyed using the online form by employing cluster random sampling. Each cluster is based on the district where respondents work in a particular district junior high school. This study finds that transformational leadership's total and direct effects on organizational culture exist. However, organizational culture does not mediate the relationship between transformational leadership and organizational culture. It implies that policymakers should design a system to strengthen the role of organizational culture in organizational commitment. Future research may involve more variables in the existing model, such as job satisfaction and organizational commitment, by employing a structural equation model.